Latin American &Amp; Caribbean Petroleum Engineering Conference 2007
DOI: 10.2118/107184-ms
|View full text |Cite
|
Sign up to set email alerts
|

Past Technologies Emerge Due to Lightweight Proppant Technology: Case Histories Applied on Mature Fields

Abstract: In mature fields, operators are often seeking ways to increase the hydrocarbon recovery, with the help of reputable service companies. Well stimulation continues to be, by far, the preferred method of achieving such goal. Operators and service companies are continually screening out technologies which will deliver the highest benefit/cost ratio for a particular stimulation well treatment, maintaining focus on operational and health, safety and environment excellencies. This paper addresses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Then high fracture conductivities were attained with the low concentration range. 32 These results indicated that the composite particles had a potential application as one kind of ultralightweight proppants.…”
Section: Apparent Density Analyses Of Pmma/sf Composite Particlesmentioning
confidence: 83%
“…Then high fracture conductivities were attained with the low concentration range. 32 These results indicated that the composite particles had a potential application as one kind of ultralightweight proppants.…”
Section: Apparent Density Analyses Of Pmma/sf Composite Particlesmentioning
confidence: 83%